Limitada atención de los padres de familia en el desarrollo académico de los estudiantes de la escuela de Educación Básica Dr. Luis Poveda Orellana, de la parroquia El Progreso, cantón Pasaje, periodo lectivo 2012-2013. - Illescas Valarezo, Roger Antonio (2013)
The opening for authority and teachers of the School of Basic Education Dr. Luis Poveda Orellana, allowed to develop this research has generated expectations in the context that served as the basis for its realization, its conceptual theoretical content points out issues that define the importance the family of the student within the educational process, and within it the first knowledge she being the first school of human life are taught.